The Implementation of Merdeka Curriculum in English Subject at the Seventh Grade Students of SMPN 1 Ampek Angkek - Julianti, Uci; Reflinda, Reflinda; Melani, Melyann; Roza, Veni (Pusdikra-Publishing.com, 2025)
This research was conducted based on the problems which were found by the researcher at the seventh grade of SMPN 1 Ampek Angkek. First, teacher difficulties in understanding and creating syllabus. Second, teacher difficulties challenges in comprehending the content of the new textbooks merdeka curriculum. Third, the delayed arrival of books at school leads teacher to use the previous curriculum books, eventhough the merdeka curriculum has been implemented in the school. The study aims to determine how teacher the planning, implementation, and evaluation of the curriculum in class and to find the teacher’s problem during the implementationn of the merdeka curriculum in English subject at seventh grade of SMPN 1 Ampek Angkek.This research was Descriptive Qualitative research. The instruments of this research were observation checklists and interviews. The informant of this research was teacher who taught at the seventh grade in SMPN 1 Ampek Angkek. The data were obtained from two class observation in four meeting from seventh grade and interview with English teacher. To analyzed the data, researcher used the theory of Miles, Huberman, and Saldana. The results of the research show that the implementation of the merdeka curriculum learning includes planning learning by identifying the availability of effective weeks, analyzing allocated learning outcomes to effective weeks, determining learning objectives and learning objective flow, and formulating teaching modules. The problem faced by Planning include difficulties in creating teaching modules, implementation challenges involve applying teaching strategies, evaluation challenges students learning outcomes remain low even though the material has been studied repeatedly.